2013
DOI: 10.21500/20112084.723
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience and ethnography: an interdisciplinary revision and a cognitive proposal based on compassion research in Mexico

Abstract: Social neuroscience considers the interplay of biologically evolved mechanisms and culturally shaped experiences as decisive to contextualize, motivate and influence complex brain functions and cognition. Compassion is a suitable moral emotion for approaching social cognition because it involves naturally and socially evolved factors to empathize with and wish to alleviate a perceived suffering of other individuals, and thereby promote social welfare. The present paper outlines research projects performed in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(66 reference statements)
0
1
0
1
Order By: Relevance
“…Dado que la compasión ha sido considerada una experiencia afectiva, distintos teóricos incluyen su estudio en el contexto de las emociones morales (Díaz-Alzate, Arbeláez-Gómez, & David-Manco, 2015;Mercadillo & Díaz, 2013;Mercadillo, Díaz, & Barrios, 2007;Ostrosky-Solís & Vélez-García, 2008;Saavedra, Mola, Gancedo, Belaus, & Reyna, 2013). Las emociones morales están conformadas por relaciones y juicios entre uno mismo y los demás.…”
Section: Introductionunclassified
“…Dado que la compasión ha sido considerada una experiencia afectiva, distintos teóricos incluyen su estudio en el contexto de las emociones morales (Díaz-Alzate, Arbeláez-Gómez, & David-Manco, 2015;Mercadillo & Díaz, 2013;Mercadillo, Díaz, & Barrios, 2007;Ostrosky-Solís & Vélez-García, 2008;Saavedra, Mola, Gancedo, Belaus, & Reyna, 2013). Las emociones morales están conformadas por relaciones y juicios entre uno mismo y los demás.…”
Section: Introductionunclassified
“…Since insular functions relate to representing internal states, empathy, and experiencing moral emotions (Mercadillo and Díaz, 2013;Mutschler et al, 2013;Decety and Cowell, 2014), its participation may involve morality and emotional processes inserted in religiosity. Furthermore, by using functional brain connectivity analysis with religious believers, it is suggested that religiosity may influence ToM and autobiographical memory.…”
mentioning
confidence: 99%